Contractor selection for performance‐based maintenance partnerships - Straub, Ab; Mossel, Henk-Jan van (International Journal of Strategic Property Management, 2010)
Dutch housing associations use new procurement methods such as performance‐based maintenance partnerships for maintaining their housing stock. Such partnerships promise a range of advantages as compared to the traditional tendering of maintenance projects. For contractors a performance‐based approach implies major changes in methods and work processes. A major change within this performance‐based approach is contractors acting as maintenance‐engineering consultants to clients. This requires new activities to be considered, such as providing advice on maintenance strategies, the design of maintenance scenarios, performance measurements and conducting customer satisfaction surveys. The execution of these activities demands additional capabilities from the contractor. The introduction of the Quality Mark for Real Estate Maintenance VGO KEUR is a first step in quality assurance of maintenance contractors in the Netherlands. It guarantees principals that contractors are able to work according performance‐based methods and procedures. A next step in quality assurance should be to establish a clear relationship between maintenance‐engineering and consulting activities and contractor's performance outcome.First published online: 18 Oct 2010